Representações cartográficas: 6º ano do ensino fundamental dos Colégios Estaduais Rodrigo Rodrigues da Cunha e Martins Borges de Pires do Rio (GO) - (:unkn) unknown (Universidade Federal de Goiás, 2017)
The insertion of the Cartography within the teaching of Geography, is something extremely relevant for the critical formation of the students. Thus, it is sought to understand the insertion proposal, and also what the student's perception of the environment in which he is present. This dissertation is based on a theoretical background focusing on the relevance of Cartography teaching in the school environment, as well as the collection of documentary data from govern of the state public education, such as the National Curriculum Parameters (NCPs), the Reference Curriculum of the State Network of Goiás and Analysis of the Pedagogical Political Projects in this country. Seeking to have a real notion of the students' understanding of the cartographic content that was taught to them and the relation that they make with experienced geographic space, the analysis of the representations of mental maps produced by students of the 6th grade from two state schools of Pires do Rio (GO). As part of the results achieved, it was possible to perceive some of the main collective difficulties expressed in the representations. One part of the research that drew much attention was the analysis of representations produced by students with special educational needs. In this way, it was possible, through the representations, to understand the perception that 6th grade students have of cartographic teaching.
Keywords: Geografia; Cartografia; Mapa mental; Ensino fundamental; Geography; Cartography; Mental map; Elementary school; GEOGRAFIA FISICA::GEOCARTOGRAFIA